ANALISIS STRATEGI PENGEMBANGAN USAHAPADA CV AGRO SUKSES ABADI EKA FARM KABUPATEN BANTUL - Shawn Noah Rashaad Santosa; Dwi Aulia Puspitaningrum (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
CV Agro Sukses Abadi Eka Farm is an organic-based health food company facing challenges in raw material management and production capacity. This study aimed to identify internal and external factors, formulate strategic alternatives, and determine the best business development strategy. A quantitative case study approach was used, with data collected through observation, FGD, interviews, questionnaires, and documentation. Analysis tools included the IFE, EFE, IE matrics, SWOT, and AHP. The results show that the company’s main strength is its wide network of raw material suppliers, while its main weakness is the absence of an offline outlet. The main opportunity lies in the availability of maquiladoras and resellers, while the main threat is competitors with wider market reach. The S-O strategies include consumer segmentation, fixed contracts with suppliers, digital marketing, and business scaling. AHP results indicate that the top priority strategy is scaling up through investor funding and partnership collaboration.